(untitled) (Research, Society and Development, 2022)
After the creation of laws and decrees that reiterate the importance of the entry of disability people into the regular education system, there was a fall in enrollment in the so-called exclusive classes and a significant increase in the so-called regular classes. Although these individuals are inserted in the school environment, inclusion has not been happening, because there are no specialized professionals and adapted pedagogical resources for students with specific educational needs. In order to impact on teacher education (initial and continued) and on the production of Chemistry adapted materials, this work aims to develop two educational resources adapted for visually impaired students on "Evolution of Atomic Models" in a partnership between the Federal Institute of Education, Science and Technology of Rio de Janeiro (IFRJ) and the Benjamin Constant Institute (IBC). The production of pedagogical resources was divided into nine stages: theme´s choice, writing, correction, adaptation, transcription, revision, texturing, printing and evaluation. During these stages, IBC professionals actively participated, highlighting the performance of blind professionals in the review and evaluation of the material. After the evaluation of visual impairment students (blind and low vision) of the ninth grade of IBC Elementary School, the materials were approved. In this work we conclude that teaching materials adapted for visually impaired students are essential in their learning process.